National Health Card as a means of improving the Unified Health System (SUS): Integrative literature review (Research, Society and Development, 2022)
The National Health Card (CNS) was created by e-Health policies, through the Ministry of Health, with the aim of promoting the integration of data from users of the Unified Health System (SUS). The objective of this research is to analyze the reason for the CNS to speed up and contribute to health care and services within the SUS. This research is an integrative literature review, carried out during the months of November and December 2022, the data used were extracted from the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Scientific Electronic Online Library (SCIELO ), Virtual Health Library (VHL) and Latin American and Caribbean Literature on Health Sciences (LILACS). The descriptors were: “Unified Health System”, “Primary Health Care” and “e-Health Policy”. The inclusion criteria were studies in Portuguese, free of charge and within the time frame from 2018 to 2022. The exclusion criteria were duplicate articles, abstracts, reviews and theses. After selecting the studies, according to the inclusion and exclusion criteria, only 6 articles were selected to compose the final sample. It was concluded that, due to the union of several data through the CNS, such as personal data, records, actions and history of the individual, such a tool speeds up care, unifies information and integrates the sectors within the SUS, being a fundamental part for the growth and development of public health policies.